Kajian Yuridis Putusan Mahkamah Agung dalam Penyelesaian Sengketa Pada Perusahaan Leasing Dengan Badan Penyelesaian Sengketa Konsumen - Azizah, Agustine (Jurnal Panorama Hukum, 2021)
The purpose of this study for reviewed the dispute resolution between the finance company and the consumer decided by BPSK in the case of Supreme Court Decision Number 210 K/Pdt.Sus-BPSK/2015 and examine the consideration of the Supreme Court Judge stating that BPSK is not authorized to decide case in between consumer financing companies.This research is normative descriptive who use secondary data and collecting data use literature study. Data analysis use interactive model.The result of the research indicates that the Supreme Court Decision Number 210 K/Pdt.Sus- BPSK/2015 in the case of special dispute on consumer dispute between First Indo American Leasing Branch Bandung ("First Indo Finance") with BPSK Bandung and Neva Rahmansyah, SE stated that The Supreme Court rejected the appeal from the First Appeal Applicant of PT First Indo American Leasing Bandung ("First Indo Finance") and amended the decision of Bandung District Court Number 461/Pdt.G/2014/PN Bdg. dated December 24, 2014 so that it is clear that the Supreme Court accepted the exception of the petitioners and stated that BPSK is not authorized to examine and adjudicate the case and to punish the Cassation Applicant Applicant to pay the court fee in the appeal level stipulated at Rp 500,000 (five hundred thousand rupiahs). Consideration of the Supreme Court Judge stating that BPSK is not authorized to decide the case in the case between the finance company and the consumer because the legal relationship between the Plaintiff and the Defendant constitutes a joint financing agreement with the fiduciary transfer of property, which implements civil law relationships and does not include consumer disputes as provided in the Act Number 8 Year 1999 on Consumer Protection so that the dispute arising from the implementation of the consumer financing agreement is a dispute agreement which is the authority of the District Court.